Семантичні особливості авторських емотивів позитивного реагування в українській поезії ХХ сторіччя - Метелюк, Ірина; Meteliuk, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано найбільш репрезентативну групу індивідуально- авторських номінацій на позначення почуттів та емоцій із позитивною конотацією, зафіксованих в українській поезії XX ст., встановлено семантичні особливості неологізмів-емотивів, виділено основні лексико-семантичні групи інновацій та з’ясовано їхню семантику. The attempt to analyze of individual-author’s names of emotions and feelings with positive and negative connotation fixed in the Ukranian poetical texts of the last century is made. The most productive classes of parts of author’s lexical new-formations are reviewed, the main lexical and semantic groups of innovations are singled out, the semantic features of occasional color names’ emotives are analyzed. The author’s lexcal new-formations using with antonymic component are dicribed. It is marked their semantics to base on contextual polarity items that make up the nominations. The distinctive stylistic features of poetic texts are the active use of individual-author’s juxtaposition with both pre-positive and postpositive signivied components.
Semantic Features of Author’s Emotives of Positive and Negative Reacting in Ukranian Poetry of XX Century.
Keywords: авторський лексичний новотвір; лексична інновація; оказіональне слово; лексико-семантична група; author’s lexical new-formations; lexical innovation; occasional word; lexical and semantic group